Marsupial cathelicidins: characterization, antimicrobial activity and evolution in this unique mammalian lineage - Peel, Emma; Gonsalvez, Adele; Hogg, Carolyn J.; Belov, Katherine (Frontiers in Immunology, 2025)
IntroductionCathelicidins are a family of antimicrobial peptides well-known for their antimicrobial and immunomodulatory functions in eutherian mammals such as humans. However, cathelicidins in marsupials, the other major lineage of mammals, have received little attention despite lineage-specific gene expansions resulting in a large and diverse peptide repertoire.MethodsWe characterized cathelicidins across the marsupial family tree and investigated genomic organisation and evolutionary relationships amongst mammals. Ancestral sequence reconstruction was used to predict ancestral marsupial cathelicidins, which, alongside extant peptides, were synthesized and screened for antimicrobial activity.ResultsWe identified 130 cathelicidin genes amongst 14 marsupial species representing 10 families, with gene expansions identified in all species. Cathelicidin genes were encoded in a highly syntenic region of the genome amongst all mammals, although the number of gene clusters differed amongst lineages (eutherians one, marsupials two, and monotremes three). 32 extant and ancestral marsupial cathelicidins displayed rapid, potent, and/or broad-spectrum antibacterial and antifungal activity. Phylogenetic analysis revealed that marsupial and monotreme cathelicidin repertoires may reflect both mammals and birds, as they encode non-classical cathelicidins found only in birds, as well as multiple copies of neutrophil granule protein and classic cathelicidins found only in eutherian mammals.ConclusionThis study sheds light on the evolutionary history of mammalian cathelicidins and highlights the potential of wildlife for novel bioactive peptide discovery.